Feminine Feminists : Cultural Practices in Italy - Jeffries, Giovanna Miceli (Book collections on Project MUSE., 1994)
What does it mean to be a woman today in Italy, a country with the lowest birthrate in the world and the heaviest maternal stereotype? Does being a feminist exclude practices of cultural femininity? These questions are at the center of this volume, which looks at how feminism and femininity are embedded in a broad spectrum of Italian cultural practices.